TOURISM MARKETING, A WAY TO PROMOTE TOURISM IN THE AREA OF COCLESITO - Pedreschi Caballero, Ricardo Jesús; Nieto Lara, Oris Mercedes (Centros: Revista Científica Universitaria, 2023)
This article tries to identify the importance and strategies that companies or businesses can use to promote a tourist destination to a target audience. The main objective of the investigation is to inform tourists about the different tourist places that the Coclesito community offers since, as we know, it is not a well-known place in terms of internal tourism. The purpose of tourism marketing is to identify, categorize and evaluate the latent or real demand for the products and services that a company provides or can provide to focus the development, production, marketing, and sales efforts of a tourist destination. A very important aspect for tourism marketing is to inform potential customers about the benefits of visiting a particular place and at the same time provide them with travel options, so it is necessary to put those interested in contact with people trained to provide them with a quality service.